The Second Law, Gibbs Free Energy, Geometry, and Protein Folding - Fang, Yi (JOURNAL OF ADVANCES IN PHYSICS, 2014)
The fundamental physical law of protein folding is the second law of thermodynamics. The key to solve protein folding problem is to derive an analytic formula of the Gibbs free energy. It has been overdue for too long. Let U be a monomeric globular protein whose M atoms 1 M a are classified into hydrophobicity classes H H , ,H 1 H 2.